Multicenter Study of Outcomes Among Persons With HIV Who Presented to US Emergency Departments With Suspected SARS-CoV-2. (1st December 2021) - Bennett, Christopher L.; Ogele, Emmanuel; Pettit, Nicholas R.; Bischof, Jason J.; Meng, Tong; Govindarajan, Prasanthi; Camargo, Carlos A.; Nordenholz, Kristen; Kline, Jeffrey A.; ,
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: There is a need to characterize patients with HIV with suspected severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Setting: Multicenter registry of patients from 116 emergency departments in 27 US states. Methods: Planned secondary analysis of patients with suspected SARS-CoV-2, with (n = 415) and without (n = 25, 306) HIV. Descriptive statistics were used to compare patient information and clinical characteristics by SARS-CoV-2 and HIV status. Unadjusted and multivariable models were used to explore factors associated with death, intubation, and hospital length of stay. Kaplan–Meier curves were used to estimate survival by SARS-CoV-2 and HIV infection status. Results: Patients with both SARS-CoV-2 and HIV and patients with SARS-CoV-2 but without HIV had similar admission rates (62.7% versus 58.6%, P = 0.24), hospitalization characteristics [eg, rates of admission to the intensive care unit from the emergency department (5.0% versus 6.3%, P = 0.45) and intubation (10% versus 13.3%, P = 0.17)], and rates of death (13.9% versus 15.1%, P = 0.65). They also had a similar cumulative risk of death (log-rank P = 0.72). However, patients with both HIV and SARS-CoV-2 infections compared with patients with HIV but without SAR-CoV-2 had worsened outcomes, including increased mortality (13.9% versus 5.1%, P < 0.01, log-rank P < 0.0001) and their deaths occurred sooner (median 11.5 versus 34 days, P < 0.01). Conclusions: Among emergency department patients with HIV, clinical outcomes associated with SARS-CoV-2 infection are not worse when compared with patients without HIV, but SARS-CoV-2 infection increased the risk of death in patients with HIV.